2018
DOI: 10.1016/s2352-4642(17)30151-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Healthy Lifestyles Programme (HeLP) to prevent obesity in UK primary-school children: a cluster randomised controlled trial

Abstract: SummaryBackgroundAlthough childhood overweight and obesity prevalence has increased substantially worldwide in the past three decades, scarce evidence exists for effective preventive strategies. We aimed to establish whether a school-based intervention for children aged 9–10 years would prevent excessive weight gain after 24 months.MethodsThis pragmatic cluster randomised controlled trial of the Healthy Lifestyles Programme (HeLP), a school-based obesity prevention intervention, was done in 32 schools in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 21 publications
2
82
1
10
Order By: Relevance
“…Both reviews identified a need for further high-quality studies. More broadly, our findings also differ from those reported by more recent school-based childhood obesity prevention studies in the UK that included a physical activity element [34,35]. These trials did not find evidence of multicomponent interventions having any impact on reducing BMIz or obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…Both reviews identified a need for further high-quality studies. More broadly, our findings also differ from those reported by more recent school-based childhood obesity prevention studies in the UK that included a physical activity element [34,35]. These trials did not find evidence of multicomponent interventions having any impact on reducing BMIz or obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the promise of schools as a universal context to influence health behaviours, our review and emerging trial evidence, suggest that current efforts are not having an impact. It is unlikely that we will make substantial changes to population levels of, and inequities in, physical inactivity and obesity in children by focusing our collective efforts on only one setting, such as schools, when the wider environments are insufficiently supportive for behaviour change .…”
Section: Discussionmentioning
confidence: 99%
“…The baseline anthropometric measurements, although similar and with considerable overlap, were greater on average in the intervention group, with 12.1% and 14.6% of the intervention group classified as overweight and obese, respectively, compared with 10.7% and 12.6% of the control group. Reproduced from Lloyd et al 32 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: http://creativecommons.org/licenses/by/4.0/.…”
Section: Results (Primary and Secondary Outcomes)mentioning
confidence: 99%
“…Reproduced from Lloyd et al 32 This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: http://creativecommons.org/ licenses/by/4.0/.…”
Section: -Month Measuresmentioning
confidence: 99%
See 1 more Smart Citation